Comparative Analysis of the Stock Performance of Digital Banks and Conventional Banks in Indonesia - Ahmad Rizki Fauzan (Sekolah Tinggi Manajemen IPMI, 2023)
Digitalization in the banking sector shows enormous growth, and the rise of digital banks may be a solution to boost financial inclusion in Indonesia. In recent years, digital banks in Indonesia seem to attract the banking sector, which is reflected in the bank transformation. This study aims to compare digital and conventional banks' risk-adjusted stock performance in Indonesia using commonly used performance measure ratios, such as Sharpe, Treynor, Sortino, and Jensen. Panel data regression with performance ratios as the dependent variables was constructed in this study. The main outcome of this study shows that the performance of digital banks tends to be better than conventional banks. Additionally, the size of banks, return on equity (ROE), and non-performing loans (NPL) tend to be positively associated with risk-adjusted performance. One of the limitations of this research is the absence of prior research on the digital bank. As a result, exploratory research on digital banking can be conducted